GROWTH RESPONSE, BIOCHEMICAL COMPOSITION AND FATTY ACID PROFILES OF FOUR ANTARCTIC MICROALGAE SUBJECTED TO UV RADIATION STRESS - Chiew-Yen, Wong; Wan-Loy, Chu; Marchant, Harvey; Siew-Moi, Phang (Malaysian Journal of Science, 2004)
The effects of ultra-violet radiation (UVR) stress on the growth, biochemical composition and fatty acid profiles of four Antarctic microalgae from the University of Malaya Algae Culture Collection (UMACC) were investigated. The microalgae studied were Chlamydomonas UMACC 229, Navicula UMACC 231, Chlorella UMACC 237 and Klebsormidium UMACC 227 which were isolated from samples collected from Casey Station, Antarctica. Three experiments were conducted. In the first experiment, the cultures were exposed to to days of high UVB (515 Ã‚ÂµWcmÃ¢ÂÂ»Ã‚Â²) + Photosynthetically Active Radiation (PAR), UVA (845 Ã‚ÂµWcmÃ¢ÂÂ»Ã‚Â²) + PAR, and PAR alone. In the second experiment, the cultures were illuminated for to days with low UVB (117 Ã‚ÂµWcmÃ¢ÂÂ»Ã‚Â²) + PAR and PAR alone. In the third experiment, the cultures were subjected to short-term (48 hours) exposure of low UVB (117 Ã‚ÂµWcmÃ¢ÂÂ»Ã‚Â²) + PAR and PAR alone. There was no marked difference amongst the four Antarctic microalgae in terms of their growth response to UVB. All the species tested did not grow well after exposure to low (117 Ã‚ÂµWcmÃ¢ÂÂ»Ã‚Â²) or high (515 Ã‚ÂµWcmÃ¢ÂÂ»Ã‚Â²) UVB for 10 days. In contrast, exposure of UVA at 845 Ã‚ÂµWcm-2 for to days did not affect the growth of the microalgae. Growth of the cultures exposed to UVA for 48 h was only slightly affected compared to those exposed to PAR alone. The effects of UVR on lipid, carbohydrate and protein content did not show consistent trends. However, exposure to UVB resulted in marked decrease of the percentage of polyunsaturated fatty acids (PUFA) in the four microalgae. Thus, fatty acid profile is a distinct biomarker for UVR stress.